Impact of social media on e-reputation – analysis of Marriott hotel chain in Algeria - Bessouh, Nadira; Grari, Yamina; Boukli-Hacene, Ghizlene (Management and Entrepreneurship: Trends of Development, 2024)
This research aims to examine the impact of social media on the e-reputation of Marriott hotels in Algeria, while focusing on electronic word-of-mouth. The main purpose is to analyze the way interactions on digital platforms can affect customer perception and, consequently, the online reputation of establishments. A literature review was conducted to develop a conceptual framework specific to Marriott hotels' activities on social media. In addition, interviews were conducted with 125 customers who stayed in these hotels. The collected data were processed with SmartPls software, which provided a comprehensive understanding of the relationships between social media, electronic word-of-mouth, and e-reputation. The findings indicate that social media play a crucial role in building the e-reputation of hotels. In particular, positive reviews published online are strongly correlated with an improved perception of the quality of services offered in these hotels. It must be emphasized that this study was limited to the analysis of social media and word-of-mouth, without taking into account other equally important factors, such as the process of monitoring and engagement on social networks, which deserve to be further exploited. On the practical side, the results obtained are highly valuable for hotel managers, community managers, and stakeholders in the tourism sector, because they provide them with leads that help them maximize customer satisfaction and loyalty. Finally, the originality of this research on hospitality and social media lies in its orientation on the Algerian market which, in our opinion, remains little studied. JEL Classification: M31, O33, Z33